Assessment of biological activity of the caffeine‐derived Pt (II) and Pd (II) complexes. (6th December 2021) - Jovanović‐Stević, Snežana; Ćoćić, Dušan; Puchta, Ralph; Bogojeski, Jovana; Jurišević, Milena; Gajović, Nevena; Jakovljević, Slobodan; Arsenijević, Nebojša; Jovanović, Ivan; Petrović, Biljana
Abstract: The substitution reactions of [Pd (caffeine)2 Cl2 ] and [Pt (caffeine)2 Cl2 ] (caffeine = 1, 3, 7‐trimethylxanthine) complexes with bio‐molecules such as 9‐methylguanine (9‐MetGua) and guanosine‐5′‐monophosphate (5′‐GMP) were studied spectrophotometrically. Kinetic measurements were performed under the pseud o‐first‐order conditions at 37°C and pH = 7.2 (25‐mM Hepes buffer) with the addition of 50‐mM NaCl. All reactions were carried out in two reaction steps giving the [M (caffeine)2 (Nu)2 ] (M = Pd (II) or Pt (II) and Nu = 5′‐GMP or 9‐MetGua) as the reaction product. The reaction mechanism was also confirmed by nuclear magnetic resonance (NMR) spectroscopy and density functional theory (DFT) calculations. Kinetically data revealed a much higher reactivity of [Pd (caffeine)2 Cl2 ] complex compared with analog platinum‐complex, while 9‐MetGua reacted faster than 5′‐GMP. The interactions of [Pd (caffeine)2 Cl2 ] and [Pt (caffeine)2 Cl2 ] complexes with calf thymus‐DNA (CT‐DNA) and human serum albumin (HSA) were investigated as well. Competitive studies with DNA were performed in the presence of ethidium bromide (EB) and Hoechst dye 33258 (Hoe). The complexes interact with DNA via minor groove rather than by intercalation. High values of binding constants indicate a good binding affinity of complexes toward HSA (10 4 M −1 ). Additionally, the experimental results of binding studies between [Pt (caffeine)2 Cl2 ] complex with DNA and HSA were compared by a molecular docking study. The cytotoxicity of [Pd (caffeine)2 Cl2 ] and [Pt (caffeine)2 Cl2 ] complexes was tested against the mouse breast cancer (4T1) and colon cancer (CT26) as well as the human breast cancer (MDA‐MB‐468) and colon cancer (HCT‐116)] cell lines. The results indicate that the [Pt (caffeine)2 Cl2 ] complex has higher cytotoxic capacity compared with [Pd (caffeine)2 Cl2 ] at concentrations higher than 2 μM. Abstract : The interactions of [Pd (caffeine)2 Cl2 ] and [Pt (caffeine)2 Cl2 ] (caffeine = 1, 3, 7‐trimethylxanthine) complexes with 9‐methylguanine (9‐MetGua), guanosine‐5′‐monophosphate (5′‐GMP), calf thymus‐DNA (CT‐DNA), and human serum albumin (HSA) were studied. Much higher reactivity of [Pd (caffeine)2 Cl2 ] complex was noted, while 9‐MetGua reacted faster than 5′‐GMP. The complexes have good binding affinity to DNA and HSA. Both complexes exhibit cytotoxicity against the mouse breast cancer (4T1) and colon cancer (CT26) as well as the human breast cancer (MDA‐MB‐468) and colon cancer (HCT‐116)] cell lines.